# math

posted by .

10xy-15x^2= 5xy(2x-3)factor out GCF

• math -

I can't decide if you want to factor the equation 10xy-15x^2= 5xy(2x-3) or if you
say the GCF of 10xy-15x^2 is 5xy(2x-3)

if it is the latter than the GCF of
10xy - 15x^2 is either 5x or (2y - 5x)
depending on the values of x and y.

if you want to factor the equation, then ...
10xy-15x^2 - 5xy(2x-3) = 0
10xy-15x^2 - 10x^2y + 15xy = 0
25xy - 10x^2y = 0
5xy(5 - 2x) = 0

## Similar Questions

1. ### bobpursly,

Is this correct now after i revised it Multiply. 3xy^2(5xy-4x+6y) 3xy^2(5xy)=15x^2y^3 3xy^2(-4x)=-12x^2y^2 3xy^2(6y)=18xy^3 so i get from this 15x^2y^3-12x^2y^2+18xy^3 correct awsome i just thought that the 15x^2y^3-12x^2y^2 should …
2. ### algebra

what is the GCF of -x^9, -3x^3, -15x^5? I think the only common factor is x am I right?
3. ### GCF Math Check

Can you see if my answers are correct? Directions find the GCF: (I did the factor tree for each) 40; 2^3 times 5 128; 2^7 GCF: 2 90; 3^2 times 2 times 5 105; 5 times 3 times 7 180; 3^2 times 2^2 times 5 GCF: 5 3x^3; what is that suppose
4. ### Math

Can you see if my answers are correct? Directions find the GCF: (I did the factor tree for each) 40; 2^3 times 5 128; 2^7 GCF: 2 90; 3^2 times 2 times 5 105; 5 times 3 times 7 180; 3^2 times 2^2 times 5 GCF: 5 3x^3; what is that suppose

5xy^2 + 15x^2y^2 - 25xy^2 + 65x^2y^2 = 10x^2y^2 + 45xy^2 Factor out the GcF of each polynomial in the equation

5xy^2 + 15x^2y^2 - 25xy^2 + 65x^2y^2 = 10x^2y^2 + 45xy^2 Factor out the GcF of each polynomial in the equation